Detection of Degenerative Changes in the Articular Disc of the Temporomandibular Joint Using Delayed Gadolinium- Enhanced MRI at 3 Tesla – A Case Report - Eder, Jaryna; Schmid-Schwap, Martina; Szomolanyi, Pavol; Bristela, Margit; Skolka, Astrid; Piehslinger, Eva; Trattnig, Siegfried (The Journal of Dentists, 2018)
The delayed Gadolinium-Enhanced Magnetic Resonance Imaging of Cartilage (dGEMRIC) is a useful tool for the evaluation of a repair tissue status after cartilage transplantation. A previous study showed the feasibility of dGEMRIC at 3 Tesla in TMJ. This case report describes the application of dGEMRIC to a TMD patient. A 27 years old female patient reported TMJ (VAS 87) with increasing intensity. The examination according to RDC/TMD showed myofacial pain (group I) and arthralgia of the right and left joint (IIIa). The graded chronical pain score showed grade III. The conventional MRI showed no sign of discus dislocation. T2 mapping showed a significant signal in homogeneity in both disci, as well as an increased amount of fluid in both compartments and a flattened disc in the lateral area. The application of dGEMRIC with patients suffering from temporomandibular disorders could be very well suited for early detection of onset pathological change in fibrocartilage.